Best Practices Layanan Telemedisin Rumah Sakit Yayasan dalam Pemenuhan Hak Kesehatan - Prananingrum, Dyah Hapsari; Prasetyo, Abigail; Yanto, Oliviani; Putri, Kezia Annabel Rinda (Widya Yuridika, 2025)
This research analyzes the fulfillment of health rights through telemedicine services by Foundation Hospitals. The best practice of telemedicine services by Panti Wilasa Citarum Hospital is carried out as a form of citizens' right to health as mandated in the Constitution. The best practice of hospital telemedicine is in line with the character of the foundation that prioritizes humanitarian values and is not for profit.  This research is an empirical juridical research that uses field studies complemented by literature studies. A purposive sampling technique was used to sample the good practice of telemedicine in Panti Wilasa Citarum Hospital. Primary data was collected by interviewing the director and the doctor in charge of telemedicine, while secondary data was collected by literature study. After the data is collected, it is analyzed qualitatively. From this study, the fulfillment of patient health rights in telemedicine services is in principle subject to the 1945 Constitution, Law Number 17 of 2023 concerning Health and implementing regulations governing patient rights. The findings in this study are that the Foundation Hospital or Panti Wilasa Citarum Hospital, the best practices carried out have described practices that refer to a model of excellence in telemedicine services that can be utilized by other hospitals as a model for telemedicine and the government in formulating policies that can encourage better implementation of telemedicine by Foundation Hospitals. Furthermore, the fulfillment of patient health rights in the implementation of best practices in hospital telemedicine services, in the form of being given the correct answer from the results of the examination, giving the right medicine, getting assistance if the patient is in a category that must be accompanied, and getting personal data protection. Thus, the right to health has been fulfilled through the Foundation Hospital telemedicine service.